PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI MADAM SOUVENIR - Sitorus, Arnold Rudolf; Dewi Anggraini (Universitas HKBP Nommensen, 2025)
This study aims to analyze the influence of service quality and product quality on purchasing decisions at Madam Souvenir, Medan. The population in this study were customers of Madam Souvenir. The research method used was a quantitative method and the research sample used purposive sampling. The sample used in this study was 30 people. The results of this study indicate that: 1) Service quality has a positive and significant effect on purchasing decisions at Madam Souvenir, 2) Product quality has a positive and significant effect on purchasing decisions at Madam Souvenir, 3) Service quality and product quality have a positive and significant effect simultaneously on purchasing decisions at Madam Souvenir.